Expresión de la proteína transductora de señales y activadora de la transcripción 3 (STAT 3) Y Bcl-xL en cáncer de mama - Alcalá Mota Velazco, Berenice (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The protein STAT3 has been involved in the development of breast cancer because it modulates genes involved in carcinogenesis. Bcl-xL is an anti-apoptotic protein that promotes greater survival to neoplastic cells. Both proteins are associated with poor prognosis. The aim of the present study was to associate the histological, molecular and clinical stage type with the expression of nuclear STAT3 and Bcl-xL proteins in breast cancer. In tumor microarrays (TMA) of 310 cases of breast cancer, the nuclear STAT3 protein phosphorylated (pSTAT3) and cytoplasmic and nuclear Bcl-xL, were analyzed by inmunohistochemistry. Nuclear expression was found in 78.2% and 72% of pSTAT3 and Bcl-xL cases, respectively. In analyzing the expression of nuclear pSTAT3 in relation to the histological type, statistically significant differences (P = 0.001) and with the clinical stage (P = 0.03) were found, but not with the molecular subtype (P = 0.52). A protective factor of nuclear pSTAT3 was found between IIA and IIB stages (RR, 0.68; IC 95%, 0.517-0.893; P = 0.014), and relative risk between stages IIA and IIIA (RR, 2,696; IC 95%, 1,169-6.218; P = 0.006); as well as between stages N0 and N1 (RR 1,845; IC 95%, 1.123-3.029; P = 0.006). The expression of total Bcl-xL (nuclear and cytoplasmic) showed no statistically significant differences with the histological type (P = 0.06 and P = 0.20), with the molecular subtype (P = 0.14 and P = 0.70) or with the clinical stage (P = 0.56 and P = 0.15). The results of this study suggest that STAT3 has a dual function in breast cancer, as it presents both as a protective factor in early clinical stages and as a risk factor in locally advanced clinical stages.

La proteína STAT3 se ha visto implicada en el desarrollo del cáncer de mama porque modula genes implicados en la carcinogénesis. Bcl-xL es una proteína antiapoptótica que favorece mayor supervivencia a las células neoplásicas. Ambas proteínas se asocian con mal pronóstico. El objetivo de este estudio fue asociar el tipo histológico, molecular y estadio clínico con la expresión de las proteínas STAT3 nuclear y Bcl-xL en cáncer de mama. Mediante inmunohistoquímica en microarreglos de tumores (TMA) de 310 casos de cáncer de mama, se analizaron la proteína STAT3 nuclear fosforilada (pSTAT3) y Bcl-xL citoplasmática y nuclear. Se encontró expresión nuclear en 78.2% y 72% de los casos de pSTAT3 y Bcl-xL, respectivamente. Al analizar la expresión de pSTAT3 nuclear en relación al tipo histológico, se encontraron diferencias estadísticamente significativas (P = 0.001) y con el estadio clínico (P = 0.03), pero no con el subtipo molecular (P = 0.52). Se encontraron un factor protector de pSTAT3 nuclear entre los estadios IIA y IIB (RR, 0.68; IC 95%, 0.517-0.893; P = 0.014) y riesgo relativo entre los estadios IIA y IIIA (RR, 2.696; IC 95%, 1.169-6.218; P = 0.006); así como entre los estadios N0 y N1 (RR 1.845; IC 95%, 1.123-3.029; P = 0.006). La expresión de Bcl-xL total (nuclear y citoplasmática) no mostró diferencias estadísticamente significativas con el tipo histológico (P=0.06 y P=0.20), con el subtipo molecular (P=0.14 y P=0.70) ni con el estadio clínico (P=0.56 y P=0.15). Los resultados de este estudio sugieren que STAT3 tiene una función dual en el cáncer de mama, ya que se presenta como un factor de protección en estadios clínicos tempranos y como factor de riesgo en estadios clínicos localmente avanzados.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-R-M-2020-0530; Tipo histológico; Estadio clínico; Subtipo molecular; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3019